Students Difficulties in Solving Fraction Operations in Elementary School - Rahmawati, Azmi Siwi; Wahyudin (International Conference on Elementary Education, 2022)
Fractions is one of the competencies that elementary school students must have. One of the materials on fractions is arithmetic operations fraction. The concept of arithmetic operations fraction is important for student because there are many mathematical aspects related to the concepts and operations of fractions that are needed in everyday life. However, it was found that many students had difficulty in learning the concept of arithmetic operations fraction. The purpose of this study is to describe the difficulties experienced by students and the factors that cause students difficulties in completing arithmetic operations fraction for elementary school students. The method used in this research is a literature study. The subject of this research is an article related to students' difficulties in completing arithmetic operations fraction. Data collection using documenting and reviewing articles related to students' difficulties in completing arithmetic operations fraction. Based on this study, it was found that students had difficulty changing and simplifying fractions, difficulties in calculating addition and subtraction of fractions with unequal denominators, difficulties in understanding the concepts of multiplication and division and when solving fraction story problems. Factors that cause these difficulties are external factors from teacher factors, environment and internal factors within students.